Analysis of Life Style Representation in the â€œInterchangeâ€ English Language Teaching Books - Hosseinifar, Aida (Richtmann Publishing, 2012)
This paper tries to analyze how ideology presented in the Interchange English language teaching books is reflected. And I waslooking for the answer of this question that